Effect of Injected Charges in Polydimethylsiloxane Films on Triboelectric Power Generation - Ryuto Takita; Kaito Koshiji; Hiroki Kokubo; Winadda Wongwiriyapan; Takashi Ikuno (My University, 2021)
Towards the application of stand-alone power supplies for wearable sensors, we have investigated the effect of fixed charges in a dielectric polymer film of a triboelectric device on the output power.Our device is composed of an aluminum (Al) plate and a polydimethylsiloxane (PDMS) film.Using a corona discharge gun, we injected negative charges into the PDMS film.To maximize the output power, we optimized the corona discharge conditions.The output voltage and output power of the device using the charged PDMS film fabricated under the optimum conditions were 4.5 and 20 times higher than those of the device using the pristine PDMS film, respectively.
Keywords: Polydimethylsiloxane; Advanced Sensor and Energy Harvesting Materials